2009
DOI: 10.1017/s1751731108003868
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evaluation of Ethiopian Boran cattle and their crosses with Holstein Friesian in central Ethiopia: milk production traits

Abstract: Breed additive and non-additive effects, and genetic parameters of lactation milk yield (LYD), 305-day milk yield (305YD), lactation length (LL), milk yield per day of lactation (DM) and lifetime milk yield (LTYD) were estimated in Ethiopian Boran cattle and their crosses with Holstein in central Ethiopia. The data analyzed included 2360 lactation records spread over 15 years. Ethiopian Boran cattle were consistently inferior (P , 0.01) to the Ethiopian Boran-Holstein crosses for the dairy traits studied. When… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
31
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 13 publications
(30 reference statements)
16
31
4
Order By: Relevance
“…The present study was in agreement with a number of works considering life time milk yield (Demeke et al, 2004;Million et al, 2006;Kefena et al, 2006;Haile et al, 2009). The comparison among the crossbreds revealed that, F 1 (50% HF x 50% Boran or 50% Jersey x 50% Boran) were superior to F 2 -inters (50% HF x 50% Boran or 50% Jersey x 50% Boran).…”
Section: Genetic and Non-genetic Effectssupporting
confidence: 92%
See 4 more Smart Citations
“…The present study was in agreement with a number of works considering life time milk yield (Demeke et al, 2004;Million et al, 2006;Kefena et al, 2006;Haile et al, 2009). The comparison among the crossbreds revealed that, F 1 (50% HF x 50% Boran or 50% Jersey x 50% Boran) were superior to F 2 -inters (50% HF x 50% Boran or 50% Jersey x 50% Boran).…”
Section: Genetic and Non-genetic Effectssupporting
confidence: 92%
“…Multiple regression analysis (SAS, 2002) was used to estimate crossbreeding parameters. For the regression analysis, coefficients of expected breed content and heterozygosity in the cow were fitted as covariates to obtain estimates of the individual additive (giF or giJ), individual heterosis (hiBF or hiB) and maternal heterosis (hmBF or hmBJ) effects using similar procedures to those of Hirooka and Bhuttyan (1995), Kahi et al (2000) and Haile et al (2009).…”
Section: Heritability Genetic and Phenotypic Correlationsmentioning
confidence: 99%
See 3 more Smart Citations